State-of-the-Art, and Perspectives of, Silver/Plasma Polymer Antibacterial Nanocomposites - Kratochvíl, Jiří (Antibiotics (Basel), 2018)
Urgent need for innovative and effective antibacterial coatings in different fields seems to have triggered the development of numerous strategies for the production of such materials. As shown in this short overview, plasma based techniques arouse considerable attention that is connected with the possibility to use these techniques for the production of advanced antibacterial Ag/plasma polymer coatings with tailor-made functional properties. In addition, the plasma-based deposition is believed to be well-suited for the production of novel multi-functional or stimuli-responsive antibacterial films.